Factors of improved swimming performance by wearing a triathlon wetsuit - Tomikawa, M.; Nomura, T. (1st International Scientific Conference of Aquatic Space Activities, 2008)
This study was aimed to clarify the effects of wearing a triathlon wetsuit (WS) on performance-determining factors during swimming and to determine the factors in improved swimming performance during triathlon races when wearing a WS. Less power to overcome drag was required at a given velocity and triathletes were able to swim in faster speed. Furthermore, wearing a WS could delay accumulation of fatigue by lessening the energy used for buoyancy and postural stability, and work completed by the arms increased without increasing entire exercise intensity in a WS condition. Therefore, improved swimming performance by wearing a WS was attributable merely to the utmost use of the limited physical performance capacity, i.e. the improvement in propulsion efficiency, and was dependent more on incremental changes in stroke rate than stroke length.